The analysis of ergonomic task demand and psychosocial work factors towards occupational safety and health - Abd Aziz, Siti Fardaniah; Selamat, Mohd Nasir; Mukapit, Mukhiffun; Baker, Rogis; Jaaffar, Amar Hisham (Human Resource Management Academic Research Society, 2021)
The increase in cases of accidents at workplace, the absence of employees to the work, the rise in illness and high job stress give signs that more urgent action should be taken. If the situation that causes this problem continues, it will certainly also have negative impacts not only on employees, but also on organizations and parties directly related to employees. Occupational safety and health (OSH) aspects are key issues that need to be addressed by organizations. Previous studies have also shown that ergonomics plays an important role with OSH issues and problems, especially in the manufacturing sector. The implementation of certain initiatives based on ergonomics may provide a way of solving, or alleviating users, safety and health problems in the workplace. This study aimed to examine the ergonomic task demands and psychosocial work factors (PWF) of OSH performance in printing companies. The use of a combination of measurement tools from previous studies has resulted in a special design of questionnaire for this study. Respondents who participated in the study were selected by using stratified random sampling at the printing companies. Two hundred and ninety five respondents from several printing companies in Malaysia were surveyed and analysed. The findings showed that most of the employees were not aware of issues related to ergonomics at work. It was also found that higher job demands contribute to employee stress, accidents and lead to absenteeism problems which representing OSH performance. In addition, the findings showed that shows that PWF (decision authority & social support) are negatively related to OSH performance. Therefore, several initiatives should be taken by organisation to enhance employee’s performance especially in regards to implementation of ergonomics aspects as well as safety and health components.